Monitoring training status in cyclists using maximal rate of heart rate increase - Bellenger, C.; Thomson, R.; Howe, P.; Karavirta, L.; Buckley, J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Changes in maximal rate of HR increase (rHRI) have recently been found to correlate with fatigue-induced changes in exercise performance (1). The purpose of this study was to evaluate whether within-individual changes in rHRI can track changes in exercise performance resulting not just from fatigue, but across a range of training states. Methods: rHRI was assessed during 5 mins of cycling at 100 W and 5 mins of running at 8 km/h in male cyclists/tri-athletes following 2 weeks of light-training (LT), 2 weeks of heavy-training (HT) and a 2 day recovery period (RP). rHRI was the first derivative maximum of a sigmoidal curve fit to the HR data recorded. Exercise performance and peak oxygen consumption (VO2peak) were measured during a 5 min cycling time-trial. Results: 13 participants completed the study. Exercise performance decreased by 2.5% (P=0.016) following HT, and then increased by 4% (P=0.006) following RP. Cycling rHRI decreased by 17% (P=0.01) following HT, and remained unchanged following RP. Running rHRI remained unchanged following HT and RP. Pre-exercise HR and steady-state HR were 5 bpm (P=0.019) and 10 bpm (P=0.003) lower during cycling than running. Changes in exercise performance between LT and HT were correlated with changes in running rHRI (r=0.66, P=0.03), but not with changes in cycling rHRI. Cycling and running rHRI were not correlated with exercise performance when analysed within-subjects, however the strength of the within-subject relationship between running rHRI and exercise performance was inversely associated with VO2peak measured after LT (r=-0.58, P=0.05), such that rHRI tended to track changes in exercise performance more strongly within individuals who had a lower VO2peak. Discussion: Running rHRI, but not cycling rHRI, was able to track fatigue-induced changes in exercise performance following HT. This may be due to running rHRI being assessed at a higher exercise intensity than cycling rHRI, which is supported by the finding of a stronger within-subject relationship between rHRI and exercise performance in individuals with a lower VO2peak, as rHRI assessment in these individuals would represent a higher relative exercise intensity.